ENHANCING STUDENTS’ ATTITUDE IN PHYSICS THROUGH THE USE OF COMBINED PHYSICAL AND INQUIRY VIRTUAL LABORATORIES IN SECONDARY SCHOOLS IN ENUGU STATE (UNIZIK Journal of STM Education, 2019)
Research has revealed low enrolment and poor performance in Physics among secondary school students. This study compared the effects of enhancing students’ attitude in Physics through the use of combined physical and inquiry virtual laboratories in Enugu State, Nigeria. The study adopted quasi experimental research design, specifically, pre-test, post-test non-equivalent control group design was used. Two research questions guided the study and three null hypotheses were tested at 0.05 alpha level. The population of the study consists 3,206 SS2 students. 220 SS2 physics students formed the sample size. The sample was composed using two stage sampling procedure. The research instrument used in this study is Test of Science-Related Attitude Scale (TOSRA). The instrument and lesson plan were validated by three experts. The reliability index was established using, Cronbach alpha technique which yielded reliability coefficient of 0.81. Experimental group was taught using combined physical and inquiry virtual laboratory while the control group was taught using physical laboratory only. Data were collected by administering TOSRA to the participants as pre-test and post-test.  The research questions were answered using mean and standard deviation, while the null hypotheses were tested using Analysis of Covariance (ANCOVA). The findings showed that the use of combined Physical and Inquiry Virtual Laboratories had positive effect on students’ attitude when compared to the use of only physical lab. The use of combined physical and IVL enhanced the attitude of male physics students more than their female counterparts taught the same way. Based on the findings it was recommended that teachers should expose physics students to inquiry virtual lab activities so as to promote meaningful learning, discovery learning and learning by experience among students. Also teachers should make teaching and learning of physics gender friendly by adopting the use of CPIVL in teaching physics concepts.
Keywords: Physical Laboratory; Inquiry Virtual Laboratory; Attitude